ISO 9000 IMPLEMENTATION AND PERCEIVED ORGANISATIONAL OUTCOME: THE CASE OF A SERVICE ORGANISATION - Jasni Abdul Latif; Hazman Shah Abdullah (Asian Academy of Management Journal, 2003)
The study examines the relationship between the perceptions of the employees about ISO 9000 implementation and perceived organisational outcomes. A conceptual framework linking the level of employee influence and involvement, their perception of ISO 9000 and the perceived impact on their work and the organisational outcomes is posited. Data was collected from a random sample of 64 employees of a service organisation. Contrary to expectations, the work impact of ISO 9000 was not correlated with the efficiency and market outcomes of ISO 9000 certification but the employee involvement, influence and perception of ISO 9000 were. The conceptualization of the influence path of ISO 9000 implementation on the organisational outcomes may require rethinking as perception may have a direct effect on the outcomes without the mediation of the impact on work. In short, employees may report benefits or positive outcomes even though no change is reported in their work.